247 Regulation of Iron Homeostasis in Porcine Alveolar Macrophages Limits the Availability of Iron for Bacteria. (7th December 2018) - Du, H; Gan, Z; Ma, W; Tang, X
Abstract: Iron is a critical determinant in host-pathogen interplay because it affects cell-mediated immune pathways while also representing an essential nutrient for microbes. The aim of current study was to determine the metabolic changes of macrophage iron homeostasis following the infection of porcine alveolar macrophages 3D4/2 with intracellular and extracellular bacteria in vitro. Western blot, real-time quantitative PCR, transmission electron microscopy (TEM) and immunofluorescence microscopy were employed to evaluate iron metabolism following bacterial infection. When macrophages were challenged with intracellular bacteria Salmonella typhimurium, an expression of the principal iron export protein, ferroportin (FPN) was enhanced, and a subsequent iron efflux in Salmonella-infected phagocytes were increased (P < 0.01). However, the transcripts of iron regulatory gene hepcidin (P < 0.05), iron storage related gene ferritin-H (P < 0.01) and iron import transport-related gene Nramp (P < 0.05) were all decreased. These modulations reduced both the cytoplasmatic labile iron and the ferritin storage iron pool within macrophages (P < 0.05), thus restricting the acquisition of iron by S. typhimurium. In contrast, when challenged with extracellular bacteria E. coli K88, macrophages adopted an opposite strategy to regulate iron homeostasis, which increased the iron sequestration within macrophages and decreased the circulations of iron for E. coli K88. Our findings suggested that the different iron-regulating mechanisms of macrophages following bacterial infection aimed at withholding iron from intracellular S. typhimurium or extracellular E. coli K88, which thus limited pathogen proliferation.